Efektifitas Organisasi Dalam Pelaksanaan Tugas Kesatuan Pada Seksi Saran Dan Prasarana Satuan Brigade Mobil Kepolisian Daerah Kalimantan Tengah - Masrukin Masrukin; Ani Purwaningsih (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2015)
This research aims to obtain, process and analyze data on the effectiveness of the Organization in the implementation of unity tasks in the section of the facilities and infrastructures of regional police Mobile Brigade unit of central Kalimantan. The approach used in this research is a qualitative approach by collecting data using interview techniques, observations, and documentation. Based on the research results on the effectiveness of the Organization in the implementation of unity duties on the facilities and infrastructure section of Mobile Brigade Unit of Central Kalimantan District police was obtained that the service is given a section The infrastructure in supporting the execution of Mobile Brigade Unit task is not effective, this is due to the limitation of human resources both in terms of number of personnel or skills, limitation of facilities and infrastructure and the limitation of budget Procurement, maintenance, and freight costs, as well as limitations in the implementation of logistics activities themselves.